2006
DOI: 10.5432/jjpehss.51.421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise on arterial distensibility

Abstract: The age-related decrease in arterial distensibility, particularly central arterial distensibility, may increase systolic blood pressure and/or pulse pressure in the elderly. Previous studies have shown that daily physical activity is positively related with arterial distensibility, and that aerobic exercise training could improve arterial distensibility. Some likely biological mechanisms through which aerobic exercise improves arterial distensibility have been revealed. Thus, habitual physical activity and aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Rather, as the Chinese character for medicine (医) indicates, the results of research in this area reflect the nature of research aimed at the fulfillment of life based on the realization of human health, that is, human well-being. This is evident in Hattori (2006), Takenaka (1992), Kitagawa (1998), Matsuda (2006), Kagaya (2001), Saito (1997), andWada et al (2001). Takenaka (1992) began the discussion with the difficulty of defining stress.…”
Section: Taiiku In the Area Of Medical-natural Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Rather, as the Chinese character for medicine (医) indicates, the results of research in this area reflect the nature of research aimed at the fulfillment of life based on the realization of human health, that is, human well-being. This is evident in Hattori (2006), Takenaka (1992), Kitagawa (1998), Matsuda (2006), Kagaya (2001), Saito (1997), andWada et al (2001). Takenaka (1992) began the discussion with the difficulty of defining stress.…”
Section: Taiiku In the Area Of Medical-natural Sciencementioning
confidence: 99%
“…The basic nature of health-oriented research is also found in Kagaya (2001), Wada et al (2001), Saito (1997), and Matsuda (2006. These studies include statements such as "to determine the conditions that regulate muscle blood flow during exercise in terms of exercise characteristics" (Kagaya, 2001, p. 430), and "it is important to determine the various responses of the sympathetic nervous system to exercise in consid-A36 ering health and physical fitness from the basic standpoint of living" (Saito, 1997, p. 59), and "to provide an overview of the effect of aerobic exercise on the decrease in arterial stretch with aging and its mechanism" (Matsuda, 2006, p. 422).…”
Section: Taiiku In the Area Of Medical-natural Sciencementioning
confidence: 99%